1975
DOI: 10.2307/3897524
|View full text |Cite
|
Sign up to set email alerts
|

Response of Shortgrass Plains Vegetation to Clipping, Precipitation, and Soil Water

Abstract: Clipping shortgrass range in Texas at 2-week intervals gave 94% more forage yield than fall harvest. Clipping treatments had little effect on ground cover and plant composition. Yield was shown to be a function of current season precipitation, while plant composition and ground cover were more closely related to previous season precipitation. In the one of seven seasons when stored soil water was available at the beginning of the growing seasdn (4.91 inches of plant-available water), it was depleted by June 15. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Clipping has been shown to increase herbage yields of some species (Drawe etal. 1972;Eck et al 1975;Svejcar & Rittenhouse 1982), while very frequent clipping reduced yields and the survival of some plants (Carter & Law 1948;McLean & Wikeam 1985); our data shows that clipping treatment G significantly reduced species richness at all nutrient levels (Fig. 1A).…”
Section: Discussionsupporting
confidence: 54%
“…Clipping has been shown to increase herbage yields of some species (Drawe etal. 1972;Eck et al 1975;Svejcar & Rittenhouse 1982), while very frequent clipping reduced yields and the survival of some plants (Carter & Law 1948;McLean & Wikeam 1985); our data shows that clipping treatment G significantly reduced species richness at all nutrient levels (Fig. 1A).…”
Section: Discussionsupporting
confidence: 54%
“…Data on primary production of grasslands used in this study (Table 4) were obtained from a study which compared primary production values from a number of grassland types across the country (including types represented in Texas, Cleveland, and McCurtain counties) (Singh and Josh 1980). The values closely approximate those obtained from other studies of primary production in the state of Oklahoma (Eck et al 1975, Harlan 1960, Reigel 1947, Risser et al 1980a.…”
Section: Primary Productionsupporting
confidence: 87%
“…In addition, the palatability of the introduced grass species is Table 2). Human labor requirements are not included in the above totals but are listed in IGPP values for rangeland were obtained from Eck et al (1975). Sims and Singh (1975).…”
Section: Primary Productionmentioning
confidence: 99%
“…Hodgkinson (1976) observed increased yields in defoliated-non-irrigated Danthonia caespitosa compared with non-defoliated plants, but decreased yields with defoliation in irrigated treatment. Clipping of B. gracilis dominated grassland in Texas during the growing season compared to a senescent period resulted in large increases in production (Eck et al 1975). These authors concluded that precipitation is used most effectively if the forage produced is harvested regularly.…”
Section: Discussionmentioning
confidence: 91%